RESPON RUSIA DALAM MENANGGAPI PERLUASAN NATO DI EROPA TIMUR (1999-2022) - Dyandara Sekar Pradipta; I Nyoman Aji Suadhana Rai (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
This research aims to comprehensively analyze how Russia has responded to NATO’s expansion in Eastern Europe during the 1999–2022 period. By applying the theories of Offensive Realism and the Security Dilemma concept, this study seeks to explain the dynamic action–reaction relationship between NATO’s enlargement policies and Russia’s defense strategies within the post–Cold War geopolitical context. This research employs a qualitative method with a descriptive–analytical approach, supported by a structured interview with Alexey Golovanov, Counselor at the Embassy of the Russian Federation in Jakarta, representing the Embassy of the Russian Federation to the Republic of Indonesia, as well as an extensive literature review of various secondary sources such as policy documents, military reports, and academic publications. The findings indicate that Russia’s responses have undergone significant transformation—from defense diplomacy strategies in the early 2000s to a more confrontational policy under Vladimir Putin’s leadership. This shift is reflected in large-scale military modernization, the strengthening of strategic alliances such as the CSTO and SCO, and direct involvement in armed conflicts in Georgia (2008), Crimea (2014), and Ukraine (2022). These findings suggest that Russia’s policy is not merely a reaction to external threats but represents a long-term strategy to preserve its geopolitical influence and maintain a balance of power with NATO in the Eastern European region. Keywords: Russia, NATO, Expansion, Security Dilemma, Offensive Realism.